The Role of Teachers and the Implementation of Islamic Character Education Methods in Madrasah Students - Khairiza Fazrani (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to analyze the process of Islamic Religious Education (PAI) value internalization in the development of students’ religious character at MTs S Taman Pendidikan Islam Medan. A descriptive qualitative method was employed with data collected through observation, in-depth interviews, and document analysis. The findings reveal that value internalization is implemented through three key strategies: daily religious habituation, the integration of Islamic-based school culture, and constructive collaboration between teachers and parents in character guidance. These practices have produced a significant impact on improving worship discipline, Qur’an literacy skills, and students’ social behavior aligned with Islamic moral values. The study concludes that the success of religious character education is determined by the integration of planned value learning, strong moral modeling, and a consistently supportive educational environment.